1998
DOI: 10.1037/0033-295x.105.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Modeling memory for absolute location.

Abstract: A model for recall of location is presented that postulates 2 encoding processes: 1 producing exact (all-or-none) recall, the other resulting in inexact recall. Exact recall is modeled as the outcome of a perceptual discrimination process, and inexact recall is modeled as the incomplete outcome of a Poisson process of information gain. The model accurately predicts levels of recall and patterns of errors in a number of experiments and articulates a lawful relationship between recall and elements of picture com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Specifically, we suggest that a saliency map provides reliable anchor points by which the spatial location of objects can be cognitively represented. Because the accuracy of location memory is related to the number and proximity of anchor points (Lansdale, 1998), it follows that targets close to a number of salient features will be more accurately recalled than those more distant, as is found here.…”
Section: Discussion and Future Directionssupporting
confidence: 64%
“…Specifically, we suggest that a saliency map provides reliable anchor points by which the spatial location of objects can be cognitively represented. Because the accuracy of location memory is related to the number and proximity of anchor points (Lansdale, 1998), it follows that targets close to a number of salient features will be more accurately recalled than those more distant, as is found here.…”
Section: Discussion and Future Directionssupporting
confidence: 64%
“…Huttenlocher, Hedges, and Duncan (1991) and Lansdale (1998) have proposed elegant mathematical models of positional uncertainty and bias in memory of the location of single object. Neither of these projects was aimed at investigating the spatial reference systems used in memory, although Huttenlocher et al concluded from the distributions of memory reports that participants used polar coordinates to represent the location of a single dot in a circle.…”
Section: Alternative Theoriesmentioning
confidence: 99%
“…If matching the whole geometry is the default for young children and mature rats, as Hermer and Spelke have famously claimed [21], then it is perhaps surprising to see a role for a landmark (by which in this context we mean any feature whose relative location can be used to aid the matching process) creeping into the drop-off map-matching task, even in extremely sparse scenarios with fairly simple geometric layouts [19]. People's apparent use of such features, often apparently via some kind of propositional description of approximate relative location, may be related to the findings of an apparent tendency to code object location in both an exact and an inexact way in spatial memory [22]. The suggestion that the inexact description of relative location (depending on a landmark or other simplifying cue) may be to some extent a verbal strategy may help explain Hermer and Spelke's failure to find landmark use in their task in very young children or in rats.…”
Section: Previous Workmentioning
confidence: 97%